Face recognition door lock system / Danial Haziq Hakimi Salahuddin - Salahuddin, Danial Haziq Hakimi (2023)
The project aims to develop a secure and convenient door lock system that utilizes face recognition technology. The system's primary objective is to enhance security by accurately identifying individuals based on their facial features and granting access only to authorized personnel. The project involves designing and implementing a hardware and software solution that integrates a camera module, image processing algorithms, and a microcontroller based control unit. The camera captures the face of the person approaching the door, and the captured image is processed using facial recognition algorithms to match it against a preregistered database of authorized users. If a match is found, the door lock is automatically released, allowing entry. The system provides a reliable and efficient method of access control while eliminating the need for traditional keys or access cards, making it convenient for users. Additionally, the project considers factors such as accuracy, speed, and robustness to ensure a reliable and user-friendly face recognition door lock system